CFD based analysis of chlorination contact tank design. (2022) - Gun, Sudeshna; Chatterjee, Shilpi; Hens, Abhiram
Abstract: Chlorination is the most widely used technique for disinfecting water. Disinfection by chlorination inactivates pathogenic micro-organisms, preventing water-borne diseases. The design of a chlorination contact tank (CCT) requires precise residence time during which the chlorine passes through the tank and the consumption of a substantial quantity of chlorine during the disinfection process. The arrangements of baffles, as well as the inlet–outlet configurations, are also important which leads to the formation of a complex flow pattern causing the short-circuiting of the fluid flow and dead zone formation inside the CCT. Short-circuiting results in inefficient mixing, whereas, dead zones indicate the presence of residual chlorine in the tank. The objective of the present work is to report the preliminary results of the Computational Fluid Dynamics (CFD) analysis undertaken to investigate the hydrodynamics, turbulent transport and mixing inside the chlorination tank. Two different types of CCT geometry (rectangular and spiral) are considered for comparing the hydraulic and mixing efficiencies. Two-dimensional steady-state and time-variable numerical simulations are carried out. Species Transport modelling provides the distribution of residence time as well as chlorine concentration inside the tank. The presence of recirculation and dead zones in the chlorination tank are analysed from the velocity contour using image analysis. It was observed that amount of dead zones is significantly higher in the case of a rectangular tank when compared to a spiral one. Different hydraulic and mixing indexes were analysed in this study to compare the disinfection efficiency of the two tanks. The presence of secondary flow due to the centrifugal force facilitates the mixing process in spiral tanks.